2015
DOI: 10.1016/j.arth.2015.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Outcomes of Primary Total Knee Arthroplasty After Solid Organ Transplantation in the United States, 1998–2011

Abstract: This review of the Nationwide Inpatient Sample (1998-2011) examined trends in solid organ transplant patients who received a total knee arthroplasty (TKA) to determine whether length of stay (LOS), cost, and perioperative complications differed from non-transplant peers. Primary TKA patients (n=5,870,421) were categorized as: (1) those with a history of solid organ transplant (n=6,104) and (2) those without (n=5,864,317). Propensity matching was used to estimate adjusted effects of solid organ transplant histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Reports suggest that the hospitalization period for this patient group is longer than the patients without a transplanted organ [16]. In our study, the mean postoperative length of stay was 8.5 (5.6) days, and four patients were discharged within a similar number of days compared to the patients without a previous history of transplant surgery.…”
Section: Discussionsupporting
confidence: 45%
“…Reports suggest that the hospitalization period for this patient group is longer than the patients without a transplanted organ [16]. In our study, the mean postoperative length of stay was 8.5 (5.6) days, and four patients were discharged within a similar number of days compared to the patients without a previous history of transplant surgery.…”
Section: Discussionsupporting
confidence: 45%
“… 34 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 The strongest evidence supported increased LOS associated with perioperative risk factors. 21 , 34 , 41 , 43 , 44 , 45 , 46 , 48 , 51 , 53 , 54 , 55 , 56 , 57 , 58 …”
Section: Resultsmentioning
confidence: 99%
“…However, across surgical specialties, in comparative studies of elective surgical procedures adjusting for underlying medical comorbidity, SOT patients have similar rates of post-operative infections and wound complications [22,23]. Prior studies on complications following TJA in SOT patients have also not conclusively shown an increased risk [5,[24][25][26][27]. The reasons for this may be threefold.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, survivorship in patients who have undergone solid organ transplant (SOT) has steadily improved in part because of improvements in surgical technique and postoperative immunosuppression and surveillance protocols [ 3 ]. As SOT patients live longer, the incidence of symptomatic arthritis is likely to increase, leading to an increased demand for both primary and revision joint replacement procedures [ 4 , 5 ]. SOT patients are also at higher risk to develop femoral head avascular necrosis, patients with renal transplants, in particular, undergo THA at 5-8 times the rate of the general population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%